A heuristic approach to resource allocation - Özdamar, Linet. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1988., 1988)
The problem considered in this study is that of scheduling the activities of a project network to minimize project duration under limited resource requirements and availabilities. Various heuristic rules and optimization techniques have been applied to this problem and comparisons of their effectiveness with respect to one another have been made in the literature. However, a thorough investigation of the types of network and resource characteristics which play an underlying role in detenmining heuristic performance and which account for the variability of results has not been performed previously. The aim of this study is to specify the relationships between individual problem characteristics and heuristic perfonmance, as well as developing a new heuristic rule which will be compared with widely-used rules.
Keywords: Heuristic programming.